STRATEGI PEMASARAN PAKAN SATWA UNGGUL BLITAR - Handika Rifki W.P; Yuli Arif Tribudi; Agustina Widyaworo Kunharjati (Universitas Islam Balitar, 2016)
This study analyzes the marketing strategies of Pakan in PS SatwaUnggulBlitar views of the concept of the marketing mix.This case study research using descriptive analytic method with purposive sampling technique.Marketing mix strategy being conducted by PS Satwa Unggul are strategies related products (such as brand awareness on brand), pricing strategy (in the form of rebates), the distribution strategy (in the form of three patterns of distribution), and promotion strategies (in the form of veterinary inspection and a free counseling service) can be considered to have successfully accommodate the needs of customers with a variety of facilities and corporate excellence. Based on the research it was concluded that the strategy used in the form of improved relationships with customers through personal selling, promotion price, free inspection, extension livestock and other facilities. Suggestions for the company should maintain an edge marketing strategies implemented in the form of personal selling and promotional strategies, but it is also the company should conduct regular research on consumer behavior animal drugs that strategy actually implemented in accordance with market conditions.